Scenario-based assessment of nonfunctional requirements - Gregoriades, Andreas; Sutcliffe, Alistair G. (My University, 2005)
This paper describes a method and a tool for validating nonfunctional requirements in complex socio-technical systems. The System Requirements Analyzer (SRA) tool validates system reliability and operational performance requirements using scenario-based testing. Scenarios are transformed into sequences of task steps and the reliability of human agents performing tasks with computerized technology is assessed using Bayesian Belief Network (BN) models. The tool tests system performance within an envelope of environmental variations and reports the number of tests that pass a benchmark threshold. The tool diagnoses problematic areas in scenarios representing pathways through system models, assists in the identification of their causes, and supports comparison of alternative requirements specifications and system designs. It is suitable for testing socio-technical systems where operational scenarios are sequential and deterministic, in domains where designs are incrementally modified so set up costs of the BNs can be defrayed over multiple tests.
Keywords: Bayesian belief networks; Nonfunctional requirements validation; Scenario-based testing; Systems engineering; Algorithms; Reliability theory